Envisioning A Resilient Pakistan Gender, Intersectionality And Disaster Risk Reduction - Muhammad Sajjad (NUST Journal of Social Sciences and Humanities)
According to the United Nations Office for Disaster Risk Reduction (UNDRR), approximately 90% of climate-related deaths occur in poorer/developing countries, underscoring the urgent need for effective adaptation and risk reduction efforts (UNDRR, 2021). Adversities of climate change in Pakistan—a nation in south Asia with ~241 million people—are not a news now! Pakistan, frequently hit by several natural hazards including floods, droughts, earthquakes, and extreme heatwaves, is a country that is highly vulnerable to various disasters (Khoshnazar et al., 2023). The country's geographical diversity also contributes to its vulnerability to natural hazards. Consequently, the nation is often cited to be among the top ten countries most vulnerable to climate change, frequently experiencing devastating damages in terms of social impacts, economic adversities, and long-lasting infrastructural disruptions. For instance, the catastrophic floods of 2022 displaced millions and caused extensive damage to infrastructure and livelihoods across Pakistan (Akhtar et al., 2023). Historical events, including the 2005 earthquake and the 2010 floods, have further exposed systemic vulnerabilities in disaster preparedness and response in Pakistan.